PESAN KAMPANYE INSTAGRAM @HUMANINITIATIVE_ID DALAM MEMENGARUHI NIAT DONASI FOLLOWERS - Alghifary, Muhamad Husein; Pandu Mustikasari, Ratih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The increasing use of social media by humanitarian organizations has encouraged the development of digital campaign strategies to foster public participation in charitable activities. Human Initiative utilizes Instagram @humaninitiative_id as a platform to disseminate humanitarian campaign messages and encourage donation intention among its followers. This study aims to analyze the influence of humanitarian campaign messages on the donation intention of Instagram followers. The method used was explanatory quantitative research. Data were collected through an online questionnaire distributed to 100 active followers of @humaninitiative_id who had been exposed to the organization's humanitarian campaign content. Data analysis was conducted using normality tests, linearity tests, heteroscedasticity tests, t-tests, simple linear regression, and coefficient of determination. The results showed that humanitarian campaign messages had a significant effect on followers' donation intention. The capability of audience indicator became the most dominant factor in campaign message effectiveness, while the emotional factor emerged as the strongest indicator influencing donation intention. This study highlights the importance of delivering campaign messages that are relevant, understandable, and aligned with audience characteristics in order to encourage donation intention through social media.